KAIDAH FONOLOGIS BAHASA DAYAK IBAN: MENGUNGKAP FENOMENA METATESIS, ASIMILASI, DISMILASI, PELESAPAN DAN PERUBAHAN SUARA - Pusparini, Ni Wayan (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
This study aims to analyze the phonological rules of the Iban Dayak language, which is one of the regional languages spoken by the Iban Dayak people in Borneo. The focus of this research is to identify and describe the phoneme system of the Iban Dayak language, as well as how these phonological rules affect word structure, phonemic processes, and sound changes in everyday communication. The findings show that the Iban Dayak language has a relatively distinct system of vowels and consonants, with several phoneme variations not found in the Indonesian language. Processes such as allophony, including shifts in vowel and consonant sounds in certain phonetic environments, were observed in many word forms. Additionally, the study reveals the presence of non-contrastive phoneme distribution patterns in some linguistic contexts. This research makes an important contribution to the understanding of the phonology of the Iban Dayak language and can serve as a reference for further studies on the phonological comparison of languages within the Austronesian language family, particularly in the context of languages spoken in Borneo.